Preemptive Rights and Privatization - Frémond, Olivier; Nellis, John (World Bank, Washington, DC, 2012)
Many governments have concluded joint ventures with private investors that contain preemptive rights contractually restricting the rights to transfer ownership of a company's securities. The privatization of these joint ventures often places governments in an awkward situation. Now wishing to sell some or all of their shares, they find themselves caught between the desire to divest a good price, or at least a politically defensible one, and the need to comply with the contracts they have signed. What can they do? Depending on the amount of preemptive rights in the privatization portfolio, governments can adopt either a case-by-case approach or a more comprehensive solution. This Note sets out the options.